PEMETAAN SEBARAN TERUMBU KARANG MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI PERAIRAN ACEH UTARA - Salmarika Salmarika; Imamshadiqin Imamshadiqin; Prama Hartami (Universitas Teuku Umar, 2026)
This study aims to analyze the distribution of coral reef cover in North Aceh Waters using a Geographic Information System. This research was conducted from December 2025 to January 2026 in North Aceh Waters. Primary data collection in the field focused on in-situ water quality measurements, identification of benthic cover using Underwater Photo Transect (UPT), inventory of associated biota through visual censuses, and data collection of coral distribution coordinates. All data were then analyzed comprehensively through evaluation of quality standards for water quality, quantification of the percentage of coral cover using CPCe software, and spatial modeling of its distribution based on ArcGIS 10.8. The observation results show that the water quality including depth, temperature, salinity, pH, and DO are classified as suitable for coral reef growth in North Aceh Waters. The distribution of coral reef cover at station 1 consists of Coral namely Table Coral (Acropora sp.), Brain Coral and Massive Coral (Porites sp.), Bowl Coral (Turbinaria sp.), Encrusting Coral, various associated biota from invertebrate groups and marine flora such as blue starfish (Linckia laevigata), chicken feather anemones, and red algae. Meanwhile, at station 2, coral reef types were found consisting of Massive Coral (Porites sp.), Brain Coral (Favia sp.), Table Coral (Acropora hyacinthus), Sheet Coral (Echinopora sp.), Foliose Coral (Montipora foliosa), Encrusting Coral, and other biota were found in the form of sponges (Xestospongia muta), sea anemones, and sea cucumbers (Holothuroidea).